Urban design interventions reduce fear of crime in public spaces in gender-sensitive ways - Pablo Navarrete-Hernandez; Tom Schlesser; Davide Luca (Nature Cities, 2026)
Abstract Fear of crime in public spaces is a major policy problem worldwide. Environmental Crime Prevention proposes that modifying the built environment can reduce the fear of crime, but key questions remain: are these interventions equally effective across genders, and what intensity maximizes safety perceptions while optimizing costs? Here we evaluated three interventions: ‘Eyes on the Street’ (adding windows to blind walls), neutral stimuli (removing graffiti by repainting walls) and ‘Nature-Based Solutions’ (integrating tidy vegetation into urban infrastructure) in the context of ‘Broken Windows’ disorder. Interventions were applied at varying intensities across four types of public spaces. Using a randomized experiment in Chile with photo simulations and an adapted Positive and Negative Affective Schedule, we collected 18,150 perception ratings from 2,028 respondents. The results show that perceived safety improvements are positive but nonlinear, indicating diminishing returns beyond a certain intervention intensity. Critically, responses were highly gender specific: interventions were more effective for men, suggesting that environmental changes alone do not fully address women’s perceived insecurity.